Anthrax does not forgive mistakes: the information assessment following the yamal peninsula outbreak in the summer of 2016 - I. V. Shestakova (Журнал инфектологии, 2017)
For the first time in a long time period the sources of actual information about anthrax in Russia and in the world are systematized. The essence of the problem, features of epidemiology and clinical manifestations of the current forms of anthrax disease are analyzed. The upgraded classification of anthrax is presented, the clinical manifestations of oro-oropharyngeal varieties of intestinal form and injectable form of anthrax are described, according to extensive literature data and international guidelines and recommendations. The recommendations for clinical management of patients and diagnosis of disease are given. The need for strict compliance to the vaccination requirements of anthrax among animals and persons from risk groups is proven.